Affordable HLA-B27 Detection in Resource-Limited Settings: Evaluating Conventional PCR for Uveitis and Spondyloarthropathy in Indonesia - Nora, Rina La Distia; Edwar, Lukman; Susiyanti, Made; Aziza, Yulia; Putera, Ikhwanuliman; Sifyana, Ulifna Alfiya; Riasanti, Mei; Waliyuddin, M Zakiy; Wibawa, Maria Valentina; Ethelind, Rachel; Widodo, Erica; Sitompul, Ratna (Majalah Oftalmologi Indonesia, 2026)
Introduction: HLA-B27 is a genetic marker strongly associated with spondyloarthropathy (SpA) and acute anterior uveitis (AAU). Detection of this allele can support earlier diagnosis and targeted management. However, commercially available HLA-B27 tests are costly and often inaccessible in low- and middle-income countries, including Indonesia. Methods: A cross-sectional study was conducted involving 42 subjects: 14 with SpA, 19 with AAU, and 9 healthy controls. DNA was extracted from peripheral blood samples and analyzed using both conventional PCR (targeting exon 3 of HLA-B27) and a commercial HLA-B27 strip assay. Sensitivity, specificity, and diagnostic accuracy of conventional PCR were calculated against the commercial kit as the reference standard. Results: Conventional PCR showed high sensitivity (100%) and accuracy (85.71%) in SpA patients, indicating its potential as a reliable screening tool in this group. However, its performance in AAU patients was suboptimal, with lower sensitivity (40%) and specificity (55.56%). False positives and false negatives were observed, likely due to limitations in allele coverage by conventional primers. Conclusion: Conventional PCR is a promising, affordable alternative for HLA-B27 detection in SpA patients, particularly in resource-limited settings. However, its lower reliability in AAU cases highlights the need for careful clinical application and further optimization. Larger studies and local allele mapping are recommended to enhance diagnostic precision in diverse populations.